Ex Occidente imperium. Alexander the Great and the Mauryan Empire - Fauconnier, Bram (Histos, 2015)
Since the nineteenth century, many authors have seen the campaign of Alexander the Great in the Punjab as a pivotal moment in the history of the Indian subcontinent. British historians writing during the apex of Britain’s colonial rule perceived it as the coming of Western culture and civilization. Nationalistic Indian historians saw the Maurya Empire, which was established shortly after Alexander’s incursion, as a patriotic reaction to the foreign oppressor. This paper discusses both historiographical interpretations and questions Alexander’s role in the emerging of the Maurya Empire, emphasizing underlying structural reasons instead.